The Teaching and Learning of Social Studies in Primary and Secondary Education - Breo Tosar (Universitat Autònoma de Barcelona, 2018)
A society can only make progress if its members are educated to be intelligent, reflective thinkers and problem-solvers. . Schools play an indispensable role in this view of education. If schools are one of the key motors of progress for any society, students need to be continually challenged in the Social Studies classroom. The critical approach is key to understand Social Studies in a global and democratic society, because it is oriented to thinking reflectively about controversial issues. This approach can also be implemented through an additional language.